Efficacy and safety of apixaban vs warfarin in patients with atrial fibrillation and prior bioprosthetic valve replacement or valve repair: Insights from the ARISTOTLE trial - Guimarães, Patricia O.; Pokorney, Sean D.; Lopes, Renato D.; Wojdyla, Daniel M.; Gersh, Bernard J.; Giczewska, Anna; Carnicelli, Anthony; Lewis, Basil S.; Hanna, Michael; Wallentin, Lars; Vinereanu, Dragos; Alexander, John H.; et al. (Clinical cardiology (Mahwah, N.J.), 2019)
Background The optimal anticoagulation strategy for patients with atrial fibrillation (AF) and bioprosthetic valve (BPV) replacement or native valve repair remains uncertain. Hypothesis We evaluated the safety and efficacy of apixaban vs warfarin in patients with AF and a history of BPV replacement or native valve repair. Methods Using data from Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation (ARISTOTLE) (n = 18 201), a randomized trial comparing apixaban with warfarin in patients with AF, we analyzed the subgroup of patients (n = 251) with prior valve surgery. We contacted sites by telephone to obtain additional data about prior valve surgery. Full data were available for 156 patients. The primary efficacy endpoint was stroke/systemic embolism. The primary safety endpoint was major bleeding. Treatment groups were compared using a Cox regression model. Results In ARISTOTLE, 104 (0.6%) patients had a history of BPV replacement (n = 73 [aortic], n = 26 [mitral], n = 5 [mitral and aortic]) and 52 (0.3%) had a history of valve repair (n = 50 [mitral], n = 2 [aortic]). Among patients with BPVs, 55 were randomized to apixaban and 49 to warfarin. Among those with a history of native valve repair, 32 were randomized to apixaban and 20 to warfarin. Overall clinical event rates were low, with no significant differences between apixaban and warfarin for any outcomes. Conclusions In patients with AF and a history of BPV replacement or repair, the safety and efficacy of apixaban compared with warfarin was consistent with results from ARISTOTLE. These data suggest that apixaban may be reasonable for patients with BPVs or prior valve repair, though future larger randomized trials are needed. ClinicalTrials.gov NCT00412984.